PENGARUH ATMOSFET TOKO, CITRA MEREK DAN KUALITAS PRODUK TERHADAP LOYALITAS MELALUI KEPUASAN SEBAGAI VARIABEL INTERVENING (Studi Kasus Pada Pelanggan Distro Inspird Kota Malang) - Mega Erlinda Wulandari; M. Hufron; M. Ridwan Basalamah (UNIVERSITAS ISLAM MALANG, 2020)
ABSTRACTWhen a customer comes to a shop, the main thing that is done is to provide an assessment of the quality and price of the product offered, besides that the customer also assesses the shop's atmosphere. This is very important for the store owner to consider, because it can affect the level of customer satisfaction. In this study, the authors tried to explain the relationship between the variables Store Atmosphere, Brand Image, Product Quality, Customer Satisfaction and Loyalty Inspird customers. This research was conducted on 98 customers who had shopped at Inspird Malang Jalan Soekarno-Hatta No.D-511, Mojolangu, Lowokwaru, Malang. This type of research is explanatory research through a quantitative approach. The results showed that: 1) Store atmosphere, brand image, although not significant to customer satisfaction, while product quality has a significant effect on customer satisfaction. 2) Store atmosphere has no significant effect on Loyalty, while Brand Image and Product Quality have a significant effect on Loyalty. 3) Customer Satisfaction has a direct effect on Loyalty. 4) Satisfaction cannot mediate the influence of Store Atmosphere, Brand Image on Loyalty, while Satisfaction can mediate the influence of Product Quality on Loyalty.Keywords: Store Atmosphere, Brand Image, Product Quality, Customer Satisfaction, Loyality